2001
DOI: 10.1300/j010v33n02_03
|View full text |Cite
|
Sign up to set email alerts
|

The Cost of Caring for Patients with an Illness

Abstract: This article will examine the effects of hospital work on social workers. It will highlight the events of a focus group that was used to gather data in an attempt to begin to understand the stressors faced by the worker. The Self-Constructivist Model (McCann & Pearlman, 1990b) is utilized in relation to trauma experienced by the social worker, while working with patients diagnosed with an acute, chronic or life-threatening illness. Findings are summarized and recommendations are made to assist hospital social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 22 publications
2
28
0
Order By: Relevance
“…This may partly account for the low magnitude of correlations (the small variance in participant symptom levels overall also affects small relationship sizes). However, while social workers, disaster workers, and other professionals are trained to handle intervention-related stress, they still experience psychological effects, especially after a shared traumatic event (Dane & Chachkes, 2001;Holaday & Warren-Miller, 1995;Newhill & Sites, 2000). The need for extra support, debriefing, and training for social workers may continue long after the immediate event and increase with the amount of services provided to clients with trauma-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…This may partly account for the low magnitude of correlations (the small variance in participant symptom levels overall also affects small relationship sizes). However, while social workers, disaster workers, and other professionals are trained to handle intervention-related stress, they still experience psychological effects, especially after a shared traumatic event (Dane & Chachkes, 2001;Holaday & Warren-Miller, 1995;Newhill & Sites, 2000). The need for extra support, debriefing, and training for social workers may continue long after the immediate event and increase with the amount of services provided to clients with trauma-related problems.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, work has been focused on mental health personnel. Most studies have focused on those counseling immediate trauma victims, including sexual assault care workers (Ghahramanlou & Brodbeck, 2000;Jenkins, Mitchell, Baird, Whitfield, & Meyer, 2011;Regehr & Cadell, 1999), child protection workers (Nelson-Gardell & Harris, 2003), and hospital social workers (Dane & Chachkes, 2001). Still others are now focusing on mental health clinicians in longer-term roles, such as family therapists (Negash & Sahin, 2011) and therapists in other clinic settings.…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that prior literature has found that helping professionals who are experiencing compassion fatigue have had difficulty with their spirituality; however, in this sample, no participants indicated any issues with a decrease in their spirituality or that they relied on their spirituality as a protective measure to guard against compassion fatigue (Dane & Chachkes, 2001).…”
Section: Establishing Boundaries To Protect Aps Social Workers To Warmentioning
confidence: 64%